Southern Europe facing the single market's completion - Heinz-Jürgen Axt (Intereconomics, 1991)
The European Community is now starting the final run-up towards the completion of the single internal market by the end of 1992 and member countries are currently involved in consultations at inter-governmental conferences on the creation of economic and monetary union, and on political union. This provides an appropriate opportunity of looking at what belonging to the Community has meant so far to its new members of Greece, Portugal and Spain, and at what their chances are for the future in the light of these developments. What have their entry into the EC and the Single European Act meant to Greece, Portugal and Spain, and what lessons ought to be learned from that?
Keywords: 330